Effect of the inoculum size of microbial consortium in degrading various concentrations of tapis crude oil in soil - Siti Nursyazana Md. Salleh (Malaysian Society for Microbiology, 2021)
The objectives of this study were to optimize the size of inoculum of the microbial consortium and concentrations of Tapis crude oil for effective biodegradation. The soil without any history of hydrocarbon contamination was spiked with 5% (w/w) crude oil and added with various concentrations of microbial consortium. The size of microbial consortium was varied from 10% to 30% (v/w). Degradation of crude oil was expressed as Total Petroleum Hydrocarbon (TPH) analyzed by gas chromatography with flame ionization detector (GC-FID). The result showed the highest degradation of Tapis crude oil was at 97.8% of TPH was achieved when using 20% (v/w) of microbial consortium with 5% (w/w) of crude oil at day 10 of incubation. Further, to optimize the concentration of crude oil it was varied from 10% to 20% (w/w). For optimum concentration of crude oil with 20% (v/w) of microbial consortium produced the highest degradation when 10% (w/w) crude oil applied to the soil. The TPH degradation achieved was 100% at day 30 of incubation, meanwhile the control plot which contained only indigenous microbes showed 30% of TPH degradation at day 30 of incubation.